Direct Vision Comparison of Lip Curvature between Genders in Fully Edentulous Patients (Medico Legal Update, 2020)
Upper lip Curvature is a location of the oral commissure relative to the center of upper lip lower border. Theaim of this study was to find the relation between gender and lip curvature. A special tool had been madeto help in measurement of lip curvature. There was no significant relation between gender and curvature,however upward group was the highest one followed by straight then downward group.